(untitled) (Research, Society and Development, 2021)
The specialized literature indicates that people with autism often have difficulties in learning arbitrary relationships, taught in natural situations or taught directly in planned teaching situations, especially when using pairing attempts with the typical model, abstract stimuli or auditory stimuli. The purpose of this research project is to carry out a review of the literature on specific feeding in autism spectrum disorder, aiming to contribute to the improvement of the general state, resulting in an improvement in the teaching-learning process. This work was developed through a bibliographical survey through reading, research and textual transcriptions of national and international authors, obtained through articles of specialized scientific journals that address the topics related to education, nutrition and autism. The articles we searched for were the last 20 years. It is concluded that autism is a complex condition in which nutrition plays a key role in improving the quality of life of the individual. The various scientific studies on autistic nutrition have been contributing to the improvement of the behaviors and attitudes of these individuals.